Polypeptides Comprising Mycorrhizal Specific Esterase Bands on Maize Roots Inoculated with Four Different AMF - Sancayaningsih, Retno Peni (2009)
Abstracts Isozymes analysis in spores are used to determine inter and intra-generic species, or even isolates of AMF species. Detection of mycorrhiza in planta of some AMF species was proved by performing a Mycorrhizal Specific Isozymes (MSI) of Malate Dehydrogenase (MDH), Esterase (EST), and Glutamat Oxaloacetate Transferase (GOT) on mycorrhizal plant roots. MSI of esterase bands of AMF species in roots may vary depending on plant age. Maize inoculated with each of four AMF species, Glomus manihotis, Glomus etunicatum, Gigaspora rosea and a local isolate of Glomus sp., were used to detect MSI esterase in comparation to an uninoculated plant which were grown for 11 weeks. Esterase staining following native PAGE electrophoresis was performed initially to localize the esterase MSI band. The MSI gel bands were separated using SDS-PAGE after electroelussion to detect their comprising polypeptides. Similar Rf value (0.72) of esterase MSI band of maize roots inoculated with each AMF species are shown. These consist of four to six polypeptides with combination of 50.5, 52.7, 62.8, 65.6, 74.8, 78.2, 88.9, 110.9, 126.5, 131.8, 150.3, and 171.4 kDa. Key-words: G. manihotis, G. etunicatum, Gi. rosea